IMPLICATIONS OF PROFESSIONAL STRESS IN THE SCHOOL ENVIRONMENT - A COMPARATIVE STUDY - DENISA MANEA; CRISTIAN STAN (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. Considered to be a real threat to the modern world, occupational stress manifests a special interest regarding the teaching profession exercised in distinct school environments, respectively mass education and special education. Three instruments were used in the comparative study: the JSS questionnaire to measure professional stress (C.D. Spielberg, Ph. D. and P.R.Vayg, Ph. D), the Job Satisfaction Survey Global,( 1999, Lamond & Paul E. Spector) and a questionnaire to measure the group's cohesion-constructed by ourselves. The results showed the existence of a higher degree of professional stress in teachers from special education systems than in mass education, the professional satisfaction being inversely proportional to professional stress. The higher percentages registered in the evaluation of the teachers in mass education as compared to those in special education can be explained by the level of professional training, the teachers' expectations, the work employment type as well as the time allocated to preparation.